Residual stresses in alumina matrix composites reinforced with Ti(C, N). Issue 12 (15th June 2022) - Szutkowska, Magdalena; Cyboroń, Jolanta; Podsiadło, Marcin; Polczyk, Tomasz
Abstract: Ti(C0.5, N0.5 )-reinforced alumina matrix composites with an addition of 2 wt% ZrO2 were tested to determine residual stresses of Al2 O3 and Ti(C0.5, N0.5 ) phases. The advanced sintering technique (spark plasma sintering ―SPS) at various temperatures of 1600°C and 1700°C was used. Vickers hardness HV1, Young's modulus E, apparent density ρ and indentation fracture toughness KIC(HV) were evaluated. An indirectly residual stress measurement by the XRD method using the sin 2 ψ technique was applied. Compressive residual stresses in both phases: α-Al2 O3 and Ti(C0.5, N0.5 ) were observed. Residual stresses of α-Al2 O3(226) are in the range between −204 ± 20 MPa and −120 ± 20 MPa (for 1600 °C and 1700 °C respectively) are lower compared to Ti(C0.5, N0.5 )(420), for which the stresses are in the range of between −292 ± 20 MPa and −256 ± 20 MPa (for 1600 °C and 1700 °C respectively). The results exhibit the influence of the sintering temperature on the residual stresses of the tested phases. The residual stresses revealed at 1700°C are lower by about 40% for α-Al2 O3(226) and much less for Ti(C0.5, N0.5 )(420), by only about 15%. Microstructure studies using scanning electron microscopy, X-ray and electron diffraction phase analysis were used.